Sifat elektrikal dan thermal nanokomposit HDPE/NPCC - Dwi Wahini Nurhajati; Arum Yuniari; Emiliana Kasmudjiastuti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2011)
abstrak